Macroeconomic Effects on Economic Growth in Muslim Countries: Political System as A Moderating Variable - Arohman, Arohman; Qoyum, Abdul; Ihsan, Akmal; Andiansyah, Farma (EKONOMIKA SYARIAH : Journal of Economic Studies, 2023)
This study seeks to explore the role of the political system in supporting the influence of macro variables on economic growth in the world's Islamic countries. Data obtained from the world bank during 2010-2021. The econometric model used in the research is the Generalized Method of Moments (GMM). The main finding is that the political system has a significant negative effect on growth. This negative effect is caused by the low value of the political index determined by world governance indicators. In addition, foreign direct investment and remittances are still the main variables in supporting economic growth in the Islamic countries of the world. In contrast, interest rates show negative effects on economic growth. Further results show that an ineffective political system is unable to strengthen the relationship between foreign direct investment, remittances, and interest rates on economic growth. These findings serve as an evaluation for the 2025 OIC internal implementation action program.AbstrakStudi ini berusaha untuk mengeksplorasi peran dari sistem politik dalam mendukung pengaruh variabel makro terhadap pertumbuhan ekonomi di negara Islam dunia. Data diperoleh dari world bank selama tahun 2010-2021. Model ekonometrika yang digunakan dalam penelitian ialah generalized method of moments (GMM). Adapun temuan utamanya ialah sistem politik berpengaruh negatif signifikan terhadap pertumbuhan. Efek negatif ini disebabkan dengan rendahnya nilai indeks politik yang ditentukan oleh world governance indicators. Selain itu, investasi asing langsung dan remitansi masih menjadi variabel utama dalam mendukung pertumbuhan ekonomi di negara-negara Islam dunia. Sebaliknya, tingkat suku bunga menunjukkan efek negatif terhadap pertumbuhan ekonomi. Hasil selanjutnya ditunjukkan bahwa sistem politik yang tidak efektif tidak mampu memperkuat hubungan antara investasi asing langsung, remitansi, dan tingkat suku bunga terhadap pertumbuhan ekonomi. Temuan ini menjadi evaluasi untuk program aksi OKI 2025 yang saat ini masih berlangsung.